Reviving Kirāta Myths: Symbols and Aesthetics in Birendra Rai's Poems (Pragyajyoti, 2024)
This research article digs into the captivating realm of Kirāta myths as reflected in the selected poems of Birendra Rai. The study aims to shed light on the cultural significance of Rai's poetic works, particularly in preserving and reviving the rich tapestry of Kirāta myths, while also examining the intricate interplay of symbols and aesthetics within his selected poems. Through a comprehensive analysis, this research explores mythical elements and themes in Rai's poem, unravelling the layers of symbols and their cultural meanings. Furthermore, the article investigates the aesthetics employed by Rai, revealing how his poetic craftsmanship enhances the profound essence of Kirāta myths. Analysing the connection of aesthetics with mythical contents, this research highlights Rai's exceptional contributions to preserving Kirāta cultural heritage. The article discusses the implications of such literary endeavours for the Kirāta community, especially the Cāmliṅa Rais, and beyond. This study not only serves as a testament to the enduring power of myth and poetry but also emphasises the role of literature in safeguarding and revitalising cultural traditions for generations to come.